Yahoo奇摩 網頁搜尋

  1. 1. By using HCFC 2.Because the HCFC will destroy the ozne layer through the photo-induced scission to produce the chorine radical, which catalyzed the conversion of ozone to oxygen. 3. It cannot block the ultraviolet radiation, so it will harm the people. 4...

    分類:科學及數學 > 化學 2010年03月02日

  2. 1a) (a+1)^2 =a^2+2a+1 1b) (x+1+y)^2 =[(x+1)+y]^2 =(x+1)^2+2(x+1)(y)+y^2 =x^2+2x+1+2xy+2y+y^2 =x^2+2x+2xy+2y+y^2+1

    分類:科學及數學 > 數學 2011年10月01日

  3. 只要你找到規律,就很容易了。如下: (a+b+c)² =a²+b²+c²+2ab+2ac+bc 詳細步驟: (a+b+c)² =[(a+b)+c]² =(a+b)²+c²+2c(a+b) =a²+b²+2ab+c²+2ac+2bc =a²+b²+c²+2ab+2bc+2ac 如果是(a...

    分類:科學及數學 > 數學 2007年09月08日

  4. 1. (3x+4b)^2 = 9x^2 + 24xb + 16b^2 2. (5p+3q)^2 = (25p^2 + 30pq + 9q^2 3. (3x-y)^2 = (9x^2 - 6xy + y^2 4. (5x-4y)^2 = (25x^2 - 40xy + 16y^2 5. (7x-3y)^2 = (49x^2 - 42xy + 9y^2 6. (1-m)(1+m) = 1 - m^2 7. (m-3n)(m+3n) = m^2 - 9n^2

    分類:科學及數學 > 數學 2007年05月21日

  5. (-a+b)(-a-b) -(-a+b)(a+b) (a-b)(a+b) a^2-b^2 ____________ ((-2p+1)+q))((-2p+1)-q)) (-2p+1)^2-q^2 1-4p+4p^2-q^2 ____________________ 2010-10-24 17:29:22 補充: .

    分類:科學及數學 > 數學 2010年10月25日

  6. 簡單而言 extend是用於線性的兩維度,例如:時間,長/濶度等 expand 是用於立體或無空間限制的東西,例如:space, volume,business等

    分類:社會及文化 > 語言 2010年05月24日

  7. 當然是6y - 10 6y + (-10)是未完成的答案 2006-12-14 10:15:41 補充: 當然是-6y - 10-6y (-10)是未完成的答案

    分類:科學及數學 > 數學 2006年12月28日

  8. (-p²/4+2q³+r)² =(2q³+r-p²/4)² =(2q³+r-(p/2)²)² =[(2q³+r)-(p/2)²]² =[(2q³+r)²-2(2q³+r)(p/2)²+((p/2)²)²] =(2q^6+r²)-p²(2q³+r)/4...

    分類:科學及數學 > 數學 2007年11月09日

  9. Polystyrene IPA: /ˌpɒliˈstaɪriːn/ is an aromatic polymer made from the aromatic monomer styrene, a liquid hydrocarbon that is commercially manufactured from petroleum by the chemical industry. Polystyrene is a thermoplastic substance, normally...

    分類:科學及數學 > 化學 2008年02月29日

  10. 1) (-3x^2 + 4x) - (x - 3) = -3x^2 + 4x - x + 3 = -3x^2 + 3x +3 2) (x^2 + 2x - 5) + (-x^2 - x + 2) = x^2 + 2x - 5 - x^2 - x + 2 = x - 5 + 2 = x -3 3) (x + 2) + (x^2 + 3x - 4) - (x^2 -1) = x + 2 + x^2 + 3x - 4 - x^2 + 1 = x + 2 + 3x - 4 +1 = 4x + 2 - 4 +1 = 4x -1 4) (-x^2 - 2x + 6) - (x - 6x^2) - (-7 + 5x +4x^2) = -x^2 -2x + 6 -x + 6x^2 + 7 - 5x - 4x...

    分類:科學及數學 > 數學 2011年09月08日